Extraction of a perovskite from red mud and its photocatalytic reduction of CO2. Issue 2 (April 2023) - Li, Siwei; Liu, Wei; Zhu, Deqinq; Pan, Jian; Guo, Zhengqi; Yang, Congcong; Dong, Tao; Lu, Shenghu
Abstract: The extensive utilization of red mud is an urgent problem for the worldwide alumina plants, and the extraction of titanium from the red mud is especially difficult. The extraction of perovskite from a red mud alkaline leaching slag (by using acid leaching), in addition to its photocatalytic reduction of CO2, have been investigated in the present study. The results showed that the photocatalytic CO2 reduction performance of the extracted perovskite was like that of pure synthesized perovskite After a reaction duration of 4 h, the yields of CO and CH4 reached 10.24 μmol·g −1, 2.85 μmol·g −1, respectively, which were 0.96 times and 0.99 times that of pure perovskite, respectively. This study provides a promising method to use the titanium, as recovered from red mud, and presents a novel idea for using hazardous waste for the photocatalytic reduction of CO2, which is beneficial for the sustainable development of the alumina industry. Graphical Abstract: ga1 Highlights: Perovskite extracted from red mud alkaline leaching slag was investigated. The structural characteristics and photocatalytic performance of pure synthesized perovskite and the extracted perovskites were studied. The photocatalytic CO2 reduction performance of pure synthesized perovskite and the extracted perovskite was compared.